Pengaruh Metode Storytelling terhadap Kemampuan Bercerita pada Anak Usia 5-6 Tahun di TK Mawar Merah Sidobogem, Sugio, Lamongan - Lailatul Rohmah; Aisyah, Aisyah (CV. ULIL ALBAB CORP, 2025)
The importance of developing storytelling skills in children aged 5-6 years as part of the development of language and social-emotional skills. Storytelling is a method that has been proven to be effective in stimulating imagination, vocabulary, and improving children's speaking skills. However, the implementation of this method in PAUD institutions has not been optimal. The study aims to determine the influence of the storytelling method on the storytelling ability of children aged 5-6 years at Mawar Merah Sidobogem Kindergarten, Sugio, Lamongan. Quantitative method of pseudo-experiment with pretest-posttest control group design. The study involved two groups: the experimental group that used the storytelling method and the control group that did not use it. The data analysis technique with a paired t-test compared the results of the pre-test and posttest in both groups. Research shows a significant improvement in children's storytelling skills after the storytelling method is applied. Based on the results of the t-test, the significant value (p-value) was <0.001. because the significant value is less than 0.05 (p<0.05), H0 is rejected and H1 is accepted showing that storytelling is effective in improving storytelling skills. This method has been proven to improve storytelling skills in children aged 5-6 years, having a positive effect on children's language and social-emotional development.